2022
DOI: 10.32604/phyton.2022.018707
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Environmental Genetic Analysis of Grain Size Traits Based on Chromosome Segment Substitution Line in Rice (Oryza sativa L.)

Abstract: Grain size traits are critical agronomic traits which directly determine grain yield, but the genetic bases of these traits are still not well understood. In this study, a total of 154 chromosome segment substitution lines (CSSLs) population derived from a cross between a japonica variety Koshihikari and an indica variety Nona Bokra was used to investigate grain length (GL), grain width (GW), length-width ratio (LWR), grain perimeter (GP), grain area (GA), and thousand grain weight (TGW) under four environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…Leng et al detected five pairs of digenic epistatic interactions for rice grain size that yielded a highly phenotypic variation. They suggested that the epistatic effects should be considered during rice breeding [32]. The epistatic effects between QTLs for stigma exertion rate (qSERb3-1/qSERb6-1, qSERb3-1/qSERb8-1, and qSERb3-1/qSERb12-1) in three pyramiding lines were all positive and induced much larger pyramiding effects of 51.49%, 43.54%, and 55.51% [33].…”
Section: Identification Of Epistatic Effects Between Different Non-al...mentioning
confidence: 99%
“…Leng et al detected five pairs of digenic epistatic interactions for rice grain size that yielded a highly phenotypic variation. They suggested that the epistatic effects should be considered during rice breeding [32]. The epistatic effects between QTLs for stigma exertion rate (qSERb3-1/qSERb6-1, qSERb3-1/qSERb8-1, and qSERb3-1/qSERb12-1) in three pyramiding lines were all positive and induced much larger pyramiding effects of 51.49%, 43.54%, and 55.51% [33].…”
Section: Identification Of Epistatic Effects Between Different Non-al...mentioning
confidence: 99%